STRATEGI PENDAFTARAN MEREK DAGANG SERTA REALISASI MEREK UNTUK MENINGKATKAN REPUTASI PELAKU USAHA MIKRO KECIL MENENGAH (UMKM) BERDASARKAN UNDANG-UNDANG MEREK DAN INDIKASI GEOGRAFIS DI DAERAH JAKARTA SELATAN - Novyana, Hilda; Clarence, Jennifer; Sonya, Assyfa Putri; Halikha, Nazwa; Triana Putri, Elvira; Marchela, Amelia (Jurnal Kreatif : Karya Pengabdian untuk Masyarakat Aktif dan Inovatif, 2024)
The existence of a registered brand also provides an opportunity for UMKM to build a positive image and increase competitiveness in the market, and brand registration is an investment to protect business assets and ensure business continuity. This research aims to provide information about the importance of brands and business permits, as well as providing UMKM with the opportunity to register brands and business permits for free. The research method used in this research is a legal method, cognitive in nature with a workshop approach method, a lecture which ends with a discussion session with the community with the aim of participants getting the opportunity to understand the importance of the brand. The results of the research from this outreach were that this outreach was attended by 15 UMKM in JABODETABEK, and based on the results of the questionnaire given to 15 respondents, it can be concluded that knowledge about brands is quite extensive among them, with 100% of respondents stating that they know what a brand is. Keywords : Brand; Business Licensing; UMKM